(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2025)
This paper is an extract from a PhD dissertation on the language of humour in literary texts. The study belongs to the domain of linguistics of literary humour, a domain that has long been unrecognized due to focus on jokes as the form of humour (e.g. Raskin 1985, Zhao 1988, Zadjman 1993, Norrick 2003, Veale et al 2006 …etc.). The study deals with the linguistic analysis of humour in selected extracts from The Birthday Party (1958), and No Man’s Land (1974) by the British Nobel Prize dramatist, Harold Pinter (1930 – 2008). Incongruity has been consistently cited in the literature as the major cause of humour. It describes the cognitive basis of humour, which has its origin in the cognition of both speaker and hearer. The present research used a Complementary Pragmatic approach, with a kit of five Pragma-linguistic tools, to detect humorous incongruity in the extracts analysed. Generally, the results prove that linguistic humour in the data analysed tends to be pragmatic in that Pinter uses ordinary language extraordinarily. There is no play on words, nor breakdown of linguistic structures. Humour in the extracts analysed comes from the mismatch between the linguistic communicative strategy and the discourse context rather than from breakdown of linguistic structures.